-7(6x-6)=295

Simple and best practice solution for -7(6x-6)=295 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6x-6)=295 equation:


Simplifying
-7(6x + -6) = 295

Reorder the terms:
-7(-6 + 6x) = 295
(-6 * -7 + 6x * -7) = 295
(42 + -42x) = 295

Solving
42 + -42x = 295

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -42x = 295 + -42

Combine like terms: 42 + -42 = 0
0 + -42x = 295 + -42
-42x = 295 + -42

Combine like terms: 295 + -42 = 253
-42x = 253

Divide each side by '-42'.
x = -6.023809524

Simplifying
x = -6.023809524

See similar equations:

| 0.7(9x+7)=2.0-(x-3) | | 5+4-7=4x-2-x | | p-70=54 | | 17-2x(5-2)=13 | | 2(6)+7= | | 5y-4+5=180 | | 2(x-3)=.50(4x-12) | | 5y=179 | | 13-t+20-t=17 | | 3x-(x+31)+(1x)=-63 | | x-(-9x)=x+7 | | 2(X-8)-5(X+4)=-2(X+18) | | 4h=7+5h | | x-14(2x+5)=0 | | 5-(3+3x)-2(4-2x)=10-9(3x+2) | | x+2x+x+25=180 | | -3(-14)-8= | | -10-3m=-5m | | -4x-9=-6+1 | | a^2-b^2=25 | | -8-6z=10-9z | | (7x^2+2xy+y^7)dx+(x^2+y^6)dy=0 | | 80g+1=75g+2 | | 8n-7=9n | | 14-5x=x^2 | | 9m+8m-17m= | | 10r=10+8r | | -3(X-4)=13 | | 7x-(2x-3)=2x+12 | | -3y-8=2y+22 | | -10f=-9f-7 | | 3(d+12)=a-4d |

Equations solver categories